Development of Learning Management System with Gamification Approach for Project-Based Learning - Nugroho, Rengga Prakoso; Soepriyanto, Yerry; Wedi, Agus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This study focuses on the development of the Learning Management System for Innovation in Graphic and Visual Media with a gamification approach in the context of teaching the Graphic and Visual Media Innovation course. Currently, learning management utilizes the SIPEJAR Learning Management System (LMS) and the Progress Report Card (PRC), but their separate existence poses challenges to efficiency and effectiveness. Students are required to monitor their own learning resources and track their learning performance through the PRC. The optimal learning environment would be one in which all learning resources and progress are accessible in a single, integrated platform, allowing for convenient access from any location at any time. The objective of this research is to develop a Learning Management System (LMS) that incorporates gamification elements into project-based learning. Research design employed is Research and Development (RnD), adopting the Web-Based Instructional Design model. The sample for this research is composed of 134 students. The research was conducted between October and December. The data collected for this study is quantitative data obtained using the Technology Acceptance Model questionnaire and the level of student engagement in the learning process. The result is that students perceive the IMGV LMS as a beneficial addition to their learning experience. The LMS enables students to monitor their performance in the final course project and access assignment materials in a centralized location. Additionally, the LMS facilitates knowledge acquisition through the incorporation of quizzes, which are designed to engage students in a competitive learning environment.